Correction: Aslam et al. pH Sensitive Pluronic Acid/Agarose-Hydrogels as Controlled Drug Delivery Carriers: Design, Characterization and Toxicity Evaluation. Pharmaceutics 2022, 14, 1218 - Mariam Aslam; Kashif Barkat; Nadia Shamshad Malik; Mohammed S. Alqahtani; Irfan Anjum; Ikrima Khalid; Ume Ruqia Tulain; Nitasha Gohar; Hajra Zafar; Ana Cláudia Paiva-Santos; Faisal Raza (Pharmaceutics)
Error in Figure [...]